2017
DOI: 10.1186/s12864-017-4098-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological networks in Parkinson’s disease: an insight into the epigenetic mechanisms associated with this disease

Abstract: Background: Parkinson's disease (PD) is the second most prevalent neurodegenerative disorders in the world. Studying PD from systems biology perspective involving genes and their regulators might provide deeper insights into the complex molecular interactions associated with this disease. Result: We have studied gene co-expression network obtained from a PD-specific microarray data. The co-expression network identified 11 hub genes, of which eight genes are not previously known to be associated with PD. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…The available evidence indicates the importance of biological networks of lncRNAs and miR-NAs in PD. 26 Here, we propose for the rst time that HOTAIR promotes apoptosis by sponging miR-221 in PD. A number of investigators have reported that HOTAIR exhibits pro-apoptotic roles under various conditions.…”
Section: Discussionmentioning
confidence: 86%
“…The available evidence indicates the importance of biological networks of lncRNAs and miR-NAs in PD. 26 Here, we propose for the rst time that HOTAIR promotes apoptosis by sponging miR-221 in PD. A number of investigators have reported that HOTAIR exhibits pro-apoptotic roles under various conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Then, the eligible correlated lncRNA-mRNA pairs were choosed to construct a coexpression network by Cytoscape 3.4.0 software [19]. Moreover, conservation analysis was also performed using the R package "phastCons100way.UCSC.hg19" [20][21][22].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The alteration of gene expression contributes to the morphological and functional change of microglia during aging (Askew et al, ; Chatterjee, Roy, Bhattacharyya, & Bandyopadhyay, ; Fonken et al, ; Soreq et al, ). It is reported that there are epigenetic changes in aged mice midbrain, which elevates the inflammatory response of microglia (Chatterjee et al, ; Phillipson, ; Tang et al, ). Primed microglia are highly sensitive, which respond to neural injury more quickly and robustly with exaggerated inflammatory response that increases neuronal vulnerability under stress conditions (Fonken et al, ; Perry & Holmes, ).…”
Section: Introductionmentioning
confidence: 99%